2018
DOI: 10.1111/ctr.13250
|View full text |Cite
|
Sign up to set email alerts
|

Recent alcohol use prolongs hospital length of stay following lung transplant

Abstract: Little is known about the alcohol habits of people with advanced lung disease. Following lung transplantation, patients are asked to abstain from or minimize alcohol use. The aim of this investigation was to assess alcohol use in a cohort of patients with advanced lung disease undergoing evaluation for lung transplant. This is a prospective observational investigation comparing patient self-report of alcohol use with their responses on the Alcohol Use Disorders Identification Test (AUDIT), and alcohol biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…91 Posttransplant nutritional management challenges in these highly catabolic patients were described by Jomphe et al 92 Active casual alcohol use prevalence was about 1 in 3 prior to transplantation and was associated with a 300% increase in mechanical ventilation time and ICU stay and a 150% increase in hospital stay, but mortality and graft function outcomes were not statistically different. 93 E-cigarette use increased in this population. 94 Diabetes was extremely common in waitlisted patients (>40%) and even higher in CF waitlisted patients (>90%).…”
Section: Lung Transplantationmentioning
confidence: 82%
“…91 Posttransplant nutritional management challenges in these highly catabolic patients were described by Jomphe et al 92 Active casual alcohol use prevalence was about 1 in 3 prior to transplantation and was associated with a 300% increase in mechanical ventilation time and ICU stay and a 150% increase in hospital stay, but mortality and graft function outcomes were not statistically different. 93 E-cigarette use increased in this population. 94 Diabetes was extremely common in waitlisted patients (>40%) and even higher in CF waitlisted patients (>90%).…”
Section: Lung Transplantationmentioning
confidence: 82%
“…In a review of depression and postoperative complications, Ghoneim and O'Hara suggested several potential causes for this linkage, including association with unhealthy lifestyle, decreased compliance with medical recommendations, and tendency to seek intervention at later stages of illness [28]. Factors such as alcohol abuse, smoking, and drug abuse are known predictors of poor outcomes in surgery [28][29][30][31]. Here, although we observed higher rates of them among individuals with a history of depression, its association with mortality remained even after adjusting for these factors.…”
Section: Ta B L Ementioning
confidence: 99%
“…Each avoidable postoperative complication costs an additional $20,000 in healthcare dollars (Healy et al., 2016). Individuals with risky alcohol use and alcohol use disorders utilize the largest proportion of healthcare resources after surgery due to complications, increased hospital length of stay, and post‐operative readmissions (Graham et al., 2019; Healy et al., 2016; Lowery et al., 2018; Spies et al., 1996).…”
Section: Introductionmentioning
confidence: 99%